2021
DOI: 10.1136/jitc-2020-002007
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic features of immune checkpoint inhibitor associated myocarditis

Abstract: BackgroundMyocarditis is a highly morbid complication of immune checkpoint inhibitor (ICI) use that remains inadequately characterized. The QRS duration and the QTc interval are standardized electrocardiographic measures that are prolonged in other cardiac conditions; however, there are no data on their utility in ICI myocarditis.MethodsFrom an international registry, ECG parameters were compared between 140 myocarditis cases and 179 controls across multiple time points (pre-ICI, on ICI prior to myocarditis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 50 publications
1
30
2
2
Order By: Relevance
“…The subsequent parameters associated with diagnosis of myocarditis are electrocardiographic features. Beside ST-segment and T-wave changes, QRS duration, and QRS-T angle, the QTc interval is supposed to be associated with abnormal tissue characteristics and may play a role in risk stratification [37][38][39]. In our study, the inverse correlation between QTc duration and LVEF was revealed irrespective of the final diagnosis.…”
Section: Discussionsupporting
confidence: 47%
“…The subsequent parameters associated with diagnosis of myocarditis are electrocardiographic features. Beside ST-segment and T-wave changes, QRS duration, and QRS-T angle, the QTc interval is supposed to be associated with abnormal tissue characteristics and may play a role in risk stratification [37][38][39]. In our study, the inverse correlation between QTc duration and LVEF was revealed irrespective of the final diagnosis.…”
Section: Discussionsupporting
confidence: 47%
“…Zlotoff et al examined the ECG from a registry of myocarditis in ICI patients [20]. The study included 140 cases of myocarditis that were compared to 179 of the control cases.…”
Section: Electrocardiogrammentioning
confidence: 99%
“…Они включают синусовую тахикардию, удлинение QT, расширение QRS, нарушения проводимости, появление патологических зубцов Q, инверсию зубцов T, другие неспецифические изменения ST и T. Нормальная ЭКГ не исключает диагноз миокардита. Расширение комплекса QRS является неблагоприятным прогностическим признаком [428].…”
Section: диагностикаunclassified